Analisis Peran Komunikasi Anggota Kelompok dalam Jaringan Komunikasi - Emilia Anggriyani (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2015)
The aim of this study was to analyze the influence of farmers’ affection on adoption of innovation. The respondents used in this study were the members of Sido Rejo and Sido Mulyo groups in Bantul who had already obtained information about the innovation of compost. This research was conducted census through interviews of the object of research to obtain primary data. The influence of farmers’ affection on adoption of innovation was analyzed descriptively with sosiogram method. The results showed that both groups have one click with opinion leaders of each group leader. The conclusion of this study is the leader of the group is still the main direction in the dissemination of information in this regard as opinion leaders. Keywords: the role of communication, communication networks, groups.